2013
DOI: 10.1111/adb.12080
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine-induced endocannabinoid release modulates behavioral and neurochemical sensitization in mice

Abstract: The endocannabinoid system has been implicated in the development of synaptic plasticity induced by several drugs abused by humans, including cocaine. However, there remains some debate about the involvement of cannabinoid receptors/ligands in cocaine-induced plasticity and corresponding behavioral actions. Here we show that a single cocaine injection in Swiss-Webster mice produces behavioral and neurochemical alterations that are under the control of the endocannabinoid system. This plasticity may be the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 60 publications
4
46
1
1
Order By: Relevance
“…SR141716A has been investigated for its anti-obesity effects (Christensen et al, 2007), though has been withdrawn from the market for severe psychiatric side effects, including increased anxiety and depressed mood, effects that have been recapitulated in rat models of disordered eating (Blasio et al, 2013; Blasio et al, 2014a). CB1 antagonists/inverse agonists, including SR141716A, are also being investigated for their therapeutic potential in treating other forms of addiction (Henderson-Redmond et al, 2016; Le Foll and Goldberg, 2005), as they have been shown to modulate a variety of behaviors induced by addictive drugs, such as cocaine (Marinho et al, 2015; Mereu et al, 2015), ethanol (Economidou et al, 2006), and nicotine (Cohen et al, 2005; Le Foll and Goldberg, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…SR141716A has been investigated for its anti-obesity effects (Christensen et al, 2007), though has been withdrawn from the market for severe psychiatric side effects, including increased anxiety and depressed mood, effects that have been recapitulated in rat models of disordered eating (Blasio et al, 2013; Blasio et al, 2014a). CB1 antagonists/inverse agonists, including SR141716A, are also being investigated for their therapeutic potential in treating other forms of addiction (Henderson-Redmond et al, 2016; Le Foll and Goldberg, 2005), as they have been shown to modulate a variety of behaviors induced by addictive drugs, such as cocaine (Marinho et al, 2015; Mereu et al, 2015), ethanol (Economidou et al, 2006), and nicotine (Cohen et al, 2005; Le Foll and Goldberg, 2004). …”
Section: Discussionmentioning
confidence: 99%
“…FAAH inhibition does not alter morphine- or cocaine-induced disruptions in VTA DA cell firing or the self-administration of either drug 66, 67 . However, FAAH inhibition diminishes cocaine-induced alterations in NAc medium-spiny neuron activity 103 and this may contribute to enhanced sensitization of both cocaine-induced motor activity and mesolimbic dopamine responses following repeated cocaine exposure 68 . Other studies have investigated the effects of putative EC transport inhibitors such as AM404 and VDM11, and the findings thus far suggest that these compounds produce subtle and inconsistent effects on nicotine and cocaine reward 69–72 .…”
Section: Endocannabinoid Signaling and Rewardmentioning
confidence: 99%
“…Recent studies showed that CB1 regulates the functional balance between GABAergic inhibitory and glutamatergic excitatory synaptic inputs into VTA and NAc, which modulates dopaminergic activity to establish the addictive processes (Maldonado et al , 2006; Mereu et al , 2013). Most studies reported that the primary rewarding effects and the motivation to seek different drugs of abuse were attenuated by the inactivation of CB1 (Maldonado et al , 2006; Maldonado et al , 2013).…”
Section: Underlying Neurobiological Mechanisms For the Sex-specifimentioning
confidence: 99%